2019
DOI: 10.3390/polym11101717
|View full text |Cite
|
Sign up to set email alerts
|

Basic Properties of a New Polymer Gel for 3D-Dosimetry at High Dose-Rates Typical for FFF Irradiation Based on Dithiothreitol and Methacrylic Acid (MAGADIT): Sensitivity, Range, Reproducibility, Accuracy, Dose Rate Effect and Impact of Oxygen Scavenger

Abstract: The photon induced radical-initiated polymerization in polymer gels can be used for high-resolution tissue equivalent dosimeters in quality control of radiation therapy. The dose (D) distribution in radiation therapy can be measured as a change of the physical measurement parameter T2 using T2-weighted magnetic resonance imaging. The detection by T2 is relying on the local change of the molecular mobility due to local polymerization initiated by radicals generated by the ionizing radiation. The dosimetric sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…An example of the response curve obtained through MRI of a polyacrylamide gel (Dithiothreitol and Methacrylic Acid, MAGADIT) exposed to linear accelerator (LINAC) photons is shown in Figure 8 [ 93 ]. The effect of the Dithiothreitol oxygen scavenger was also investigated: the sensitivity reduction seen in Figure 8 with increasing dithio concentration can be attributed to interactions of this oxygen scavengers with radicals (with following reduction of the number of polymerization initiating radicals).…”
Section: Polyacrylamide Gelsmentioning
confidence: 99%
See 3 more Smart Citations
“…An example of the response curve obtained through MRI of a polyacrylamide gel (Dithiothreitol and Methacrylic Acid, MAGADIT) exposed to linear accelerator (LINAC) photons is shown in Figure 8 [ 93 ]. The effect of the Dithiothreitol oxygen scavenger was also investigated: the sensitivity reduction seen in Figure 8 with increasing dithio concentration can be attributed to interactions of this oxygen scavengers with radicals (with following reduction of the number of polymerization initiating radicals).…”
Section: Polyacrylamide Gelsmentioning
confidence: 99%
“…A dependence on the dose rate would lead to inaccurate dose maps. Some gels such as BANG-2, NIPAM, PAGAT (PolyAcrylamide Gelatin gel fabricated at ATmospheric conditions) and PASSAG (Poly 2-Acrylamido-2-MethylPropane Sulfonic acid-Sodium Salt and Gelatin) gels show response independent of dose rate, whereas some others such as MAGAT (which comprises methacrylic acid, hydroquinone, gelatin and tetrakis hydroxymethyl phosponium chloride, THPC) have a dose rate dependent response and should be used only for doses below 2 Gy [ 55 , 76 , 94 , 95 , 96 , 97 ] or for dose rates above 4 Gy/min as MAGADIT [ 93 ]. An example of the dependence of MR sensitivity on dose rate is shown in Figure 9 .…”
Section: Polyacrylamide Gelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Khan et al [25] showed one example of the use of polymer gels as dosimeters, providing a high-resolution equivalent of tissue in quality control of radiation therapy. Warman et al [26] reported the development of a device for the tomographic imaging of radio-fluorogenic gels (RFGs), which allows for scanning the 3D distribution of radiation in a gel.…”
mentioning
confidence: 99%